Spatiotemporal inventory of biogenic volatile organic compound emissions in China based on vegetation volume and production - Chi, Yan Qi; Shaodong Xie (Advanced Materials Research, 2012)
To estimate the biogenic volatile organic compound (BVOC) emissions in China, this study collected data on vegetation volume, production and distribution, converted into leaf biomass and then used BVOC emission model. In 2003, the annual BVOC emission in China was 12.83 Tg, composed of 7.45 Tg isoprene, 2.23 Tg monoterpenes, and 3.14 Tg other VOCs (OVOCs). Emissions varied significantly among plant species, with contributions ordered as follows: forests > shrubs > crops > grasslands. Southern and northeastern China were the main sources of BVOC emissions. Significant seasonal variation was found with summer contributing the most.